Environmental DNA Insights into the Spatial Status of Fish Diversity in the Mainstem of the Jialing River - Xinxin Zhou; Xiaohan Dong; Jiaxin Huang; Shuli Zhu; Weitao Chen; Yanjun Shen (Animals)
Preserving healthy river habitats is essential for maintaining fish diversity. Over time, anthropogenic activities have severely damaged river habitats, leading to notable changes in fish diversity patterns. Conducting thorough and reliable investigations into fish diversity is crucial for assessing anthropogenic impacts on diversity. In August 2023, a water ecology survey was conducted across 20 terraced river sections in the mainstem of the Jialing River, resulting in the collection of 60 environmental DNA water samples. The survey identified 99 fish species, representing 74 genera across 7 orders and 20 families, with the Cyprinidae exhibiting the highest number of species. The fish communities are predominantly composed of species inhabiting slow flowing water, demersal fish, omnivores, and fish spawning adhesive eggs. Overall, small-bodied fish dominate the mainstem of the Jialing River, and the species preferring flowing habitats are relatively scarce. In addition, geographic division analyses revealed minimal variations in fish species composition and diversity among the terraced reservoirs and across the upper, middle, and lower reaches. Notably, the fish compositions in the middle and lower reaches were found to be similar, indicating a certain degree of convergence in these sections of the Jialing River. In conclusion, this study unveils the current status and distribution pattern of fish diversity in the Jialing River and highlights the extent of anthropogenic activities’ impact on fish diversity.